Unsettling the fistula narrative: cultural pathology, biomedical redemption, and inequities of health access in Niger and Ethiopia. Issue 1 (2nd January 2017) - Heller, Alison; Hannig, Anita
ABSTRACT: Obstetric fistula, a maternal childbirth injury that results in chronic incontinence, affects an estimated one million women in the global south. In the course of media and donor coverage on this condition, fistula sufferers have been branded as 'child brides' who, following the onset of their incontinence, become social pariahs and eventually find physical and social redemption through surgical repair. This narrative framing pits the violence of 'culture' against the potency of biomedical salvation. Based on over two years of ethnographic research at fistula repair centres in Niger and Ethiopia, this paper challenges this narrative and argues that most women with obstetric fistula remain embedded in social relations, receive continued familial support, and, unexpectedly, experience ambiguous surgical outcomes. This paper interrogates the existing logics of the fistula narrative that have had the unintended effects of obscuring global structural inequalities and diverting attention away from systemic health access reforms.